Answer:
Step-by-step explanation:
haha dude ur in my class
The answer is not applicable. theres not enough information. -fvmousskaylaa
9514 1404 393
Answer:
Step-by-step explanation:
You have to realize that the absolute value function will change the sign of its argument only if that argument is negative.
108. |x -7| = x -7 . . . . . true for x-7≥0
x ≥ 7 . . . . makes the statement true
__
1a. When m < 9, the value 6m is less than 54, so 6m-54 < 0. That means the absolute value function changes the sign of its argument:
54 -6m . . . . . simplified form for m < 9
__
1b. |y -x| = y -x . . . when y > x, the argument of the absolute value is positive
Answer:
x= -12
Step-by-step explanation:
Simplifying
4x + 10 = 2x + -14
Reorder the terms:
10 + 4x = 2x + -14
Reorder the terms:
10 + 4x = -14 + 2x
Solving
10 + 4x = -14 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
10 + 4x + -2x = -14 + 2x + -2x
Combine like terms: 4x + -2x = 2x
10 + 2x = -14 + 2x + -2x
Combine like terms: 2x + -2x = 0
10 + 2x = -14 + 0
10 + 2x = -14
Add '-10' to each side of the equation.
10 + -10 + 2x = -14 + -10
Combine like terms: 10 + -10 = 0
0 + 2x = -14 + -10
2x = -14 + -10
Combine like terms: -14 + -10 = -24
2x = -24
Divide each side by '2'.
x = -12
Simplifying
x = -12
Answer:
π
Step-by-step explanation: